(untitled) (Journal of Hama University, 2022)
A total of 240 one-day-old russ broilers were exposed to green light (GL), blue light (BL), white light (WL) and mix Green Blue light (GBL), respectively, by using a light-emitting diode system for 6 wk. There were for each light treatment 60 birds per pen. The effects of monochromatic light on Productivity Indicators and the immune response were studied. The results indicated that the feed conversion factor was the best for the GBL group, which recorded a value of 1.7, followed by the GL group with a value of 1.73, then BL with a value of 1.81 and finally WL with a value of 1.83. a good behavior and Calmness was also observed on birds exposed to green and blue colors and their mixture. As for the antibody titer for Newcastle disease, the highest immunoglobulin value was recorded in the GL group at the end of the experiment compared to the other groups with significant differences (P<0.05), noting that the value increased in the first two weeks and decreased at the end of the experiment within the same group. Followed by the value of the immunoglobulins in the BL group, which gave higher immunological values at the end of the experiment compared to the beginning. While we did not observe any significant differences between the WL and BGL group, this indicates that the BL and GL groups enhance the immune response better than WL and GBL. The alternation of green color in the first half of the fattening period with blue in the second half may enhance immunity against Newcastle disease.